Ayahuasca: imaginación global y efectos locales - Caicedo-Fernández, Alhena (Ciencias sociales y religión, 2021)
Based on the idea of the globalization of ayahuasca, special emphasis has been placed on the expansion of yagé use from South America to the rest of the world. More recently, however, this expansion has been coupled with the shaping of the idea of an international ayahuasca community. As an “imagined community”, it is a space that is produced and made socially effective through particular images, metaphors and practices of representation that, I believe, need to be contemplated. In this respect, my intention in this article is to explore certain characteristics of the symbolic production that the international ayahuasca community creates and recreates, and certain powerful imaginaries that connect it with the Amazon and its inhabitants. Likewise, I am interested in delving into the way in which internationalized ayahuasca circuits are referenced, and how emblematic places appear that have become references for this community. From there, I try to characterize some effects that the globalization of ayahuasca has in the countries of the Amazon basin.